The use of state‐and‐transition models in assessing management success - Chloe F. Sato (Conservation Science and Practice, 2021)
Abstract State‐and‐transition models (STM) are valuable tools that aid understanding and management of ecosystems. There also is potential for STMs to be used as a framework to assess whether management actions are achieving desired conservation objectives. However, few published examples exist where STMs have been used in this way. Using high‐quality empirical field data collected in endangered temperate woodlands across a 6‐year period, we explore whether a Box Gum Grassy Woodland STM employed in an Australian agri‐environment scheme can be used to assess whether management interventions are achieving an improvement in woodland Condition State. We found there was insufficient contextual information in the STM to facilitate its robust use as a framework for assessing whether management interventions were achieving conservation outcomes in Box Gum Grassy Woodlands. Weather was a key driver influencing management effectiveness, but its effects were absent from the STM, as were probabilities and time frames for transitions between Condition States. The deficiencies in the STM may preclude accurate conclusions about the effectiveness of the program. Given the influence of weather on the system, longer time frames are required to adequately assess the influence of management on key variables (e.g., native plant richness, native ground cover) underpinning the STM. This case study provides opportunities to understand the potential implications of using insufficiently contextualized STMs as frameworks for assessing whether management actions are achieving desired conservation objectives. It also provides opportunities to learn from what went wrong. To this end, based on our findings, we provide practical recommendations (applicable beyond our case study system) for improving the construction and implementation of STMs for the purposes of evaluating the success of management interventions in ecological restoration and conservation programs.